Research on University Laboratory Resource Sharing and Cooperative Management (International Journal of Scientific Research and Management (IJSRM), 2024)
As the core place for technological innovation, the management level of university laboratories is directly related to the improvement of scientific research efficiency and innovation ability. This study deeply explores the current situation, problems, influencing factors, and management models of resource sharing and cooperative management in university laboratories. In terms of resource sharing, it is necessary to establish a sound resource sharing platform and mechanism; In terms of cooperation management, cooperation mechanisms and communication coordination should be strengthened; In terms of collaborative innovation, promoting innovation through interdisciplinary cooperation; In terms of knowledge management, promote knowledge acquisition, storage, and sharing. In the future, the development of digitization and intelligence will provide more opportunities for resource sharing and collaborative management. Universities should grasp the development trend, strengthen technology research and application promotion, in order to better serve technological innovation and social development.